Phonological Errors in Reading Tawasul among Cirangrang Society, Bandung District - Marlina, Lina (Institut Agama Islam Negeri Curup, 2021)
This research is a qualitative descriptive study with an analytical approach to errors in reading tawasul. This study aims to describe and analyze the form of phonological errors in reading tawasul and their causes, then formulate solutions to these errors so as to minimize errors and be able to read tawasul well, perfectly, and in accordance with the rules. The data in this study were obtained by free listening, recording, and writing techniques. They were done sequentially with several resource persons who became leaders in each activity that contained the reading of tawasul in it. From the results of observations, several errors were found in the form of addition, subtraction, and substitution of letters, tasydid, and mad signs. Additionally, some spelling errors were also found due to similarities in pronunciation, such as the letter Ø¹ becomes Ø£, letter Ø¶ becomes Ø¸, Ø® letter becomes Ø, letter Ø´ becomes Ø³, and letter Ù‚ becomes Ùƒ.